Changes in dual energy x-ray absorptiometry body composition scores in females following exercise-induced body fluid redistribution - Chacón Araya, Yamileth (2024)
This study explored how exercise-induced body fluid redistribution affects DXA body composition scores in females. Thirty participants completed upper-body, lower-body, and control sessions, with measurements taken before and after. Significant but small changes were observed in fat tissue, lean mass, and total mass, especially after upper-body exercise. These changes were consistent and reliable across conditions, indicating that fluid shifts from exercise can influence DXA results. The findings emphasize the importance of considering recent physical activity when interpreting body composition data.